Kompetensi Pedagogik Mahasiswa Pendidikan Guru Madrasah Ibtidaiyah dalam Merancang Pembelajaran - Hairunnisa, Hairunnisa; Riyawati, Mega; Winarti, Sri (BASICA Journal of Arts and Science in Primary Education, 2023)
This research illustrates the pedagogical competence of PPL (Field Experience Program) students in the PGMI program at STAI Miftahul Ulum Tanjungpinang in instructional design for primary schools (SD/MI). The study involved 35 seventh-semester students of the PGMI program who participated in the PPL during the Academic Year 2022/2023. The research employed a quantitative descriptive method with data collected through observation and questionnaires. The results indicate that students have good competence in understanding the characteristics of students, curriculum development, lesson planning and implementation, technology utilization, and evaluation of learning outcomes. From the obtained data, it is evident that the understanding of student characteristics has an average score of 88.60, categorized as very good. Understanding curriculum development obtains an average score of 86.00, categorized as very good. Lesson planning and implementation have an average score of 85.75, categorized as very good. The level of technology utilization in learning by students reaches an average score of 84.50, categorized as good. Meanwhile, the ability to evaluate learning outcomes in teaching has an average score of 87.67, categorized as very good. The PGMI educational program has successfully aligned with the standard competence of educators. This research contributes significantly to the improvement of educational programs and PPL in the future